Analysis of the Bioactive Metabolites of the Endangered Mexican Lost Fungi Campanophyllum – A Report from India. Issue 1 (2nd January 2020) - Borthakur, Madhusmita; Gurung, Arun Bahadur; Bhattacharjee, Atanu; Joshi, S. R.
Abstract: Meghalaya, (in India), in the region of the mega-biodiversity hotspots, is home to a plethora of wild mushrooms. The present study concerns the exploration of the order Agaricales, which includes rare gilled mushrooms considered endangered under IUCN A4c criteria, due to the declining habitat. Electron microscopy of the gill sections revealed an abundance of clamp connections, hyphal cell walls, cystidia, and basidia. This rare species which belongs to the family Cyphellaceae, exhibits morphological and molecular differences from the Cyphella spp. Phylogenetic analysis revealed that it formed a clade under the genus Campanophyllum of the order Agaricales, confirmed by both Neighbor Joining (NJ) and Bayesian phylogenetic analysis. Being nutritionally potent along with its efficient antioxidant value, the fungal extract shows significant rise of two-fold in the antimicrobial activity along with the commercial antibiotics. The compound, Phenol, 2, 4-bis (1, 1-Dimethylethyl) (2, 4-DTBP) showed in ample range in the fungal extract along with aliphatic hydrocarbons, terpene, alcohol and volatile organic compounds on further characterization in GCMS. The present study indicates the endangered Campanophyllum proboscideum could be a rich source of natural antioxidants and an effective pharmaceutical agent.